Attitude and Knowledge of Self-medication with Antibiotics among the Public in Riyadh, Saudi Arabia - Ballal, Rayan (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: The increase of antibiotic resistance appears as a significant risk to human health globally. Self-medication with antibiotics is described as the procurement and self-administering of antibiotics to one’s self or to children with the aim of treating an anticipated infection. Aim: The aim of this study is to determine the prevalence and incidence of self-medication with antibiotics, to explore and identify the reasons behind self-medication with antibiotics and the conditions most associated with this behavior, and to investigate the level of awareness and knowledge of this behavior among the public in Riyadh, Saudi Arabia. Methodology: This was a descriptive, cross-sectional study, and a self-administered online questionnaire has been distributed among the public in Riyadh, Saudi Arabia. Results: The prevalence rate of non-prescription antibiotic use in the past 6 months was found to be 37.4% (344/920). The results indicate that the most common reason for self-medication with antibiotics was past experience (67.4%). The most common antibiotic used for self-medication was amoxicillin/clavulanic acid and flu was the most common condition (47.83%) lead to self-medication with antibiotic in the study population. Conclusion: The majority of the study population was aware of potential adverse effects of antibiotics and yet the practice of self-medication with antibiotics was still present. Educational interventions are needed to promote the wise use of antibiotics among the public. There is a need for more strict law enforcement to limit the purchase of antibiotics without a prescription.